High myopia at high altitudes - Wang, Ta-Wei; Huang, Ming-Kun; Hsu, Chih-Chun; Jo, Szu-Yang; Lin, Yen-Kuang; How, Chorng-Kuang; Tseng, Shih-Fen; Chung, Kong; Chien, Ding-Kuo; Chang, Wen-Han; Chiu, Yu-Hui (Frontiers in Physiology, 2024)
Background: Optic nerve sheath diameter (ONSD) increases significantly at high altitudes, and is associated with the presence and severity of acute mountain sickness (AMS). Exposure to hypobaria, hypoxia, and coldness when hiking also impacts intraocular pressure (IOP). To date, little is known about ocular physiological responses in trekkers with myopia at high altitudes. This study aimed to determine changes in the ONSD and IOP between participants with and without high myopia (HM) during hiking and to test whether these changes could predict symptoms of AMS.Methods: Nine participants with HM and 18 without HM participated in a three-day trek of Xue Mountain. The ONSD, IOP, and questionnaires were examined before and during the trek of Xue Mountain.Results: The ONSD values increased significantly in both HM (p=0.005) and non-HM trekkers (p=0.018) at an altitude of 1,700 m. In the HM group, IOP levels were greater than those in the non-HM group (p=0.034) on the first day of trekking (altitude: 3,150 m). No statistically significant difference was observed between the two groups for the values of ONSD. Fractional changes in ONSD at an altitude of 1,700 m were related to the development of AMS (rpb = 0.448, p = 0.019) and the presence of headache symptoms (rpb = 0.542, p = 0.004). The area under the ROC curve for the diagnostic performance of ONSD fractional changes at an altitude of 1,700 m was 0.859 for predicting the development of AMS and 0.803 for predicting the presence of headache symptoms.Conclusion: analysis of changes in ONSD at moderate altitude could predict AMS symptoms before an ascent to high altitude. Myopia may impact physiological accommodation at high altitudes, and HM trekkers potentially demonstrate suboptimal regulation of aqueous humor in such environments.